Purification of Rubber Seed Oil Using Zeolite Adsorption Method and Noni Extract Addition - Dewi Fortuna Ayu; Yelmira Zalfiatri; Raiyan Renadi (Journal of Applied Agricultural Science and Technology, 2022)
Rubber seed oil is not currently used optimally, due to the high content of cyanide and free fatty acid. Cyanide and free fatty acid can be decrease using zeolite adsorption process and addition of noni extract. This research aims to study the effect of noni extract for cyanide and free fatty acid of rubber seed oil. Rubber seed oil was purified using the zeolite adsorption method with the addition of 10% by weight of rubber seed oil. Research method used completely randomized design which consists of 4 treatments and each treatment was repeated 4 times. The treatments of noni extract addition were 40%, 45%, 50%, and 55% of total weight of rubber seed oil. Data were statistically analyzed by using analysis of variance and continued with duncan new multiple range test at 5% level. Based on this research, the best treatment was 55% noni extract addition which had average content of cyanide 0,500 ppm, specific gravity 0,862 g/ml, and acid number 4,325 mg KOH/g.